FACTORS AFFECTING FARMER PERFORMANCE IN TRANGGULASI FARMER GROUP IN BATUR VILLAGE, GETASAN SUB-DISTRICT, SEMARANG REGENCY - Muhammad Hasan Al Bashriy; Wulan Sumekar; Siwi Gayatri (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
The aim of the study was to 1) analyze the level of farmer's performance in the Triangulasi farmer group, and 2) analyze correlation factors relating to the farmer's performance of Triangulasi farmer group members in Batur Village, Getasan Sub-District, Semarang regency. The research was conducted from October to November 2017 in the Batur village, Getasan sub-district, Semarang Regency. The method used in this research was a survey method with 32 respondents. The data were collected using questionnaires, interviews, and observations. The data analysis was usingthe Rank Spearman correlation test. The research result showed that 1) most of the members of Triangulasi farmer groups had a low-performance level, 2) the land size, farmer's motivation, and farmer's perception about the farmer group's role were not significantly related to the farmer's performance in Triangulasi of farmer group members in Batur Village, Getasan sub-District, Semarang Regency. Hence, the group leader needs to help the farmer improve product quality.